PENGARUH MODEL STATION ROTATION TERHADAP HASIL BELAJAR SISWA KELAS V MI NURUL ULUM GRABAGAN - Fauzyyah Atiqah, Firdausi Nur; Mujtahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the significant effect of the use of the station rotation model on the cognitive learning outcomes of Pancasila Education of fifth-grade students of MI Nurul Ulum Grabagan. This study is a quantitative study with an experimental research type, the research design used is a quasi-experimental design, and the form of research design used is a non-equivalent control group design. The population in the study was the entire fifth grade of MI Nurul Ulum Grabagan, totaling 49 students. The sample used in the study was the fifth grade of MI Nurul Ulum Grabagan, consisting of 24 students of class V-A and 25 students of class V-B. The sampling technique in the study used non-probability sampling with a purposive sampling technique. Data collection techniques in this study used observation and learning outcome tests. The test instruments used in this study were first tested for validity, reliability, difficulty level, and discriminatory power. The prerequisite tests used were the normality test and the homogeneity test. Hypothesis testing used the paired sample t-test. All tests in this study were calculated with the help of IBM SPSS. Based on the results of the paired sample t-test data analysis, the sig value (2-tailed) obtained was <0.0010 <0.05, so Ho was rejected. Therefore, it can be concluded that there is an influence of the station rotation model on the learning outcomes of class V students of MI Nurul Ulum Grabagan.